Chronic suppurative mandibular osteomyelitis presenting as soft tissue swelling and trismus: A case report - Ahmad, K; Ansari, S; Dhungel, K; Gupta, MK; Amanullah, MF; Kumar, A; Rauniyar, RK (Nepal Journal of Medical Sciences, 2013)
Osteomyelitis of the mandible is a rare condition and it could be a serious complication of untreated odontogenic infection. Classically, patient with osteomyelitis of the mandible would experience pain and swelling over the affected side of the face. CT is usually indicated when there is extension of the infection into the adjacent soft tissue and fascial spaces which could be the presenting clinical symptom. Hereby, we present a case of mandibular osteomyelitis in an 11 year old girl who presented with pain and swelling in left lower jaw followed by extraction of tooth, diagnosed on CT followed by surgical management. Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 | Page 197-199 DOI: http://dx.doi.org/10.3126/njms.v2i2.8978